Organisational Capabilities And Their Relationship With Organisational Performance: A Focus On The Small And Medium Industries In Malaysia. - Kuppusamy , Jayanty (2002)
The study aims to identify the relationship between organisational capabilities and organisational performance. The focus of the study was on the small and medium industries (SMIs) in Malaysia.